2023
DOI: 10.1002/pul2.12202
|View full text |Cite
|
Sign up to set email alerts
|

Metallomics in pulmonary arterial hypertension patients

Abstract: Pulmonary arterial hypertension (PAH) prevalence is increasing worldwide, and the prognosis is poor with 5‐year survival < 50% in high risk patients. The relationship between metal exposure/essential metal dyshomeostasis and PAH/right ventricular dysfunction is less investigated. The aim of this study is to investigate vegetable consumptions and metal levels between PAH patients and controls. This was a prospective, single center pilot study. Questionnaires were completed by all study subjects (20 PAH patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Prior studies also demonstrated that in vivo exposure to the thermo-oxidative degradation of ABS caused a decrease in tissue GSH level [ 87 , 88 ]. Furthermore, exposure to pollution containing Cu can also lead to GSH oxidation and depletion [ 51 , 89 ] and elevation of pro-inflammatory cytokines [ 48 , 50 , 90 ], and cause pulmonary inflammation and hypertension [ 91 ], resulting in serious respiratory diseases including COPD and pneumonia mortality [ 92 ]. Dysregulated cellular redox homeostasis is often associated with increased levels of cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies also demonstrated that in vivo exposure to the thermo-oxidative degradation of ABS caused a decrease in tissue GSH level [ 87 , 88 ]. Furthermore, exposure to pollution containing Cu can also lead to GSH oxidation and depletion [ 51 , 89 ] and elevation of pro-inflammatory cytokines [ 48 , 50 , 90 ], and cause pulmonary inflammation and hypertension [ 91 ], resulting in serious respiratory diseases including COPD and pneumonia mortality [ 92 ]. Dysregulated cellular redox homeostasis is often associated with increased levels of cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no direct evidence for the association of exposure to multiple metals with PH, there was a strong association of antimony with PAH and its associated RV pathogenesis 86 . Therefore, investigation for the potential role of metal exposure in the pathogenesis of PH, exposure to mixed metals should be considered for the epidemiological and preclinical studies 56 .…”
Section: Discussionmentioning
confidence: 99%
“…There was significant positive correlation between cardiac output and cardiac index with plasma levels of silver. There was significant correlation between mixed venous saturation, 6-min walk distance, and last B-type natriuretic peptide with plasma levels of chromium [56]. Furthermore, antimony (Sb) levels correlated with PAH severity [86].…”
Section: Metals and Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to environmental pollutants is recognized as even more important than individual genetic predisposition in causing common chronic diseases (Bhatnagar, 2006; Lamas et al, 2023; Vineis et al, 2020). However, clinically relevant toxicity is much less prevalent, and when occurring may present with non-specific symptoms, resulting in a large differential for clinicians to consider (El-Kersh et al, 2022; El-Kersh et al, 2023; Tan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%